Achievement motivation mediates the influence of knowledge management and compensation on lecturer performance - Mochamad Alvin Fikri; Agus David Ramdansyah; Ali Imron (Institute of Computer Science (IOCS), 2023)
This research aims to determine and analyze the mediating role of achievement motivation with knowledge management and compensation on the performance of lecturers at XYZ College. Quantitative research methods were used in this research with a sample of 62 permanent lecturers divided into several study programs using proportional random sampling from a total population of 165 lecturers. The data collection technique uses a questionnaire in the form of closed answers on an interval scale of 1-10 with the help of an online questionnaire which is then processed and compiled into data frequency tabulations which are then analyzed using the SmartPLS 3.2.9 program. The research results are based on direct and indirect hypothesis testing that (1) Knowledge management has a significant positive effect on lecturer performance (2) Compensation has no effect on lecturer performance (3) Knowledge management has a significant positive effect on achievement motivation (4) Compensation has a significant positive effect on achievement motivation (5) Achievement motivation has a significant positive effect on lecturer performance (6) Achievement motivation positively and significantly mediates knowledge management on lecturer performance (7) Achievement motivation significantly positively mediates compensation on lecturer performance.